2014
DOI: 10.3390/molecules19022536
|View full text |Cite
|
Sign up to set email alerts
|

Skullcap (Scutellaria baicalensis) Extract and Its Active Compound, Wogonin, Inhibit Ovalbumin-Induced Th2-Mediated Response

Abstract: Skullcap (Scutellaria baicalensis) has been widely used as a dietary ingredient and traditional herbal medicine owing to its anti-inflammatory and anticancer properties. In this study, we investigated the anti-allergic effects of skullcap and its active compounds, focusing on T cell-mediated responses ex vivo and in vivo. Splenocytes from mice sensitized with ovalbumin (OVA) were isolated for analyses of cytokine production and cell viability. Mice sensitized with OVA were orally administered skullcap or wogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 21 publications
1
32
0
4
Order By: Relevance
“…[51] Moreover, many previous works have demonstrated that Scutellaria baicalensis has significant antiallergic effects, but the detailed functions and mechanisms have not been elucidated so far. Shin et al [52] demonstrated that wogonin, an active ingredient of Scutellaria baicalensis, could downregulate the OVA-induced Th2 immune response, strongly inhibit the production of IL-5 and indirectly reduce IgE levels without reduction in cell viability. This finding might suggest that wogonin can be used as a therapeutic agent for IgE and IL-5-mediated allergic diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[51] Moreover, many previous works have demonstrated that Scutellaria baicalensis has significant antiallergic effects, but the detailed functions and mechanisms have not been elucidated so far. Shin et al [52] demonstrated that wogonin, an active ingredient of Scutellaria baicalensis, could downregulate the OVA-induced Th2 immune response, strongly inhibit the production of IL-5 and indirectly reduce IgE levels without reduction in cell viability. This finding might suggest that wogonin can be used as a therapeutic agent for IgE and IL-5-mediated allergic diseases.…”
mentioning
confidence: 99%
“…Meanwhile, they had an interesting finding that oral administration of 1 mg/kg BW of wogonin was equivalent to the administration of Scutellaria baicalensis extract at 25 mg/kg BW. [52] In 2017, Bui et al showed that the EESB (100, 200 and 400 mg/kg, p.o. ), baicalein (10 mg/kg, p.o.)…”
mentioning
confidence: 99%
“…Activation‐induced IL‐4, IL‐5 and IL‐10 secretions were lower in wogonin‐fed mice compared with control mice with DSS‐induced colitis 23. In addition, relative low dose of wogonin (50 μM) suppressed IL‐4 production of murine splenocytes in vitro and down‐regulated OVA‐induced Th2 immune responses, particularly IgE and IL‐5 secretion in vivo 24. Although Th2 cell‐associated cytokines were not observed, our results confirmed that relatively high‐dose wogonin treatment (50–100 μg/ml equivalent to 176–352 μM) promoted IFN‐ɣ production of CD4 + and CD8 + cells in the presence of IL‐2 ex vivo .…”
Section: Discussionmentioning
confidence: 92%
“…immune responses, particularly IgE and IL-5 prediction [24]. However, IFN-c and IL-2 production of T cells co-stimulated by concanavalin A and wogonin has been shown to be significantly enhanced [23].…”
mentioning
confidence: 99%
“…At present, more than 40 kinds of flavonoids have been found in Astragalus, among which Baicalein, Wogonin and Baicalin (Baicalin) and Wogonoside are high in Astragalus and have obvious pharmacological effects. Previous phytochemical studies showed that the major flavonoids in Scutellaria baicalensis are baicalin (baicalein-7-O-gluc-uronide), baicalein (5,6,7-trihydoxyflavone) [5], wogonoside and wogonin, the glycoside (baicalin) [6] can be transformed into its aglycon (baicalein) [7,8]. Both of them possess significant pharmacological activities [9], and have great potency with less toxicity in inhibiting hypertension, inflammation, allergies and hepatitis, as well as cancer [10] including lung, colorectal, prostate and breast carcinomas [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%